Minimum-Reactive-Power Scheme of Dual-Active-Bridge DC–DC Converter With Three-Level Modulated Phase-Shift Control - Shi, Haochen; Wen, Huiqing; Chen, Jie; Hu, Yihua; Jiang, Lin; Chen, Guipeng (IEEE transactions on industry applications, 2017)
This paper presents a novel reactive-power minimization method under the three-level modulated phase-shift control to improve the efficiency for a wide operation condition. First, in order to unify all operation modes, a mathematic model of the dual-active-bridge converter with the three-level modulated phase-shift control by a harmonic analysis method is obtained. Then, the detailed analysis of the odd-order harmonic components of the active and reactive powers varied with the multiple control dimensions is presented. The soft-switching boundaries with respect to the voltage ratio and unified active power are specified. On this basis, a novel optimal three-level phase-shift (OPS) control strategy for minimizing reactive power is proposed. Experimental results of reactive power and operation efficiency among the proposed OPS method, and other methods are compared to verify the effectiveness of the OPS algorithm.